REMEDIATION OF 241AM USING VETIVERIA ZIZANOIDES L. NASH: INFLUENCE OF CHELATING AGENTS : Life Science-Environmental sciences - SINGH, SHRADDHA; C. P. KAUSHIK; P. FULZELE, DEVANAND (International Journal of Life Science and Pharma Research, 2014)
The potential of Vetiveria zizanoides, a plant used for environmental conservation was tested for remediation of radionuclide americium ( 241Am) from solution and soil. Plant could remediate high levels of 241Am (62%) from solutions, remediation of radionuclides from soil was limited. Addition of chelating agents- citric acid (CA) and diethylenetriaminepentaacetic acid (DTPA) enhanced phytoremediation of 241Am from soil. Translocation of 241Am to the shoot biomass showed an enhancement in the presence of chelating agents in the solution as well as soil, whereas DTPA promoted higher translocation of radionuclides than citric acid. The present studies have shown that V. zizanoides is a suitable candidate for remediation of 241Am and addition of DTPA enhanced translocation of radionuclide to shoots.